Democracy and constitutional change - Turégano Mansilla, Isabel (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
From the premises of democratic constitutionalism, a constitutional order is legitimate not only when the mechanisms that favor inclusion, participation and deliberation are reinforced in the constituent process, but also when mechanisms are provided so that citizens can effectively participate in its development and update. The paper reviews from this perspective the debate about the diverse ways, formal and informal, in which constitutions can change. Focusing especially on the informal changes that take place through institutional interpretative practices generated from social demands, it is considered which context is more favorable to informal or formal changes of the constitution, how informal changes can be identified and whether they can have a democratic value.